The Impact of Compensation and Work Discipline on Employee Performance in Division 3 of PT. Indonesia Nippon Seiki - Nugrahaeni, Indina Dhesta; Dhesta, Indina; Alfarizi, Abdul Wahid; Wijaya, Priatna; Palahiyah, Palahiyah; Febriyani, Shoma (REVITALISASI : Jurnal Ilmu Manajemen, 2026)
This study aims to map the contributions of compensation and work discipline to the performance of employees in Division 3 of PT. Nippon Indonesia Seiki. A descriptive, non-experimental quantitative research design was employed. A saturated sampling technique was used, a choice justified by the relatively small population size of 59 individuals. Primary data analysis was conducted using a multiple linear regression model with the aid of SPSS Version 25 software. Preliminary findings indicate that compensation is not the primary factor driving employees to improve their performance; while compensation alone does not exert a significant influence on performance, it interacts with work discipline—specifically, higher levels of employee discipline result in better performance outcomes.